Identify the concentration of some heavy metal elements in different types of marine sediments dispersed on Latakia and Banias coast - كريم لايقه حسام الدين; غدير سامر غدير (Latakia University Journal -Basic Sciences Series, 2022)
This research focuses on identifying the concentration of some heavy metal elements (Lead (Pb) & cadmium (Cd)) in different types of marine sediments dispersed along Tratous coastal area using the Atomic Absorption (Atomic Absorption Spectrophotometer: AAS). The samples were collected from regions differ from each other in terms of geographical location and nature of the pollutants. The results of the research indicate a correlation between the change in the concentration of studied elements (Pb & Cd) and the nature and quality of the sand on one hand, and the different sources of pollution and its role in changing the concentration of these elements values on the other hand. The concentrations of cadmium values ​​ranged (0.036 - 0.056) mg/kg, and lead (65.53 - 97.27) mg/kg consistent with an increase in the percentage values ​​of the organic matter, and they were respectively (1.52 - 1.98)%, where the concentrations of the studied elements increased in the fine sedimentary samples. To increase the qualitative surface in the sites (St2, St3, &St4 St5) affected by sewage water compared to the rest of the sites ((St1: near the new port of Arwad) (St6: Porto Tartous tourist facility)) with fine sandy and coarse sandy sediments with the presence of straight grit. The results showed a high contamination factor Cf (Contamination Factor: Cf) in modern marine coastal sediments (3 ≤ Cf ≤ 6), indicating that the study sites fall within the high pollution of lead and the very high pollution of cadmium (Cf > 6), while the values ​​of the risk factor Environmental Er (Calculation of Ecolgical Risk: Er) indicates a low latent environmental risk for lead (Er < 40) and a significant latent environmental risk for cadmium (80 ≤ Er < 160).